2016
DOI: 10.1111/echo.13259
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Atrial Electromechanical Conduction Time Measured with Speckle Tracking Echocardiography after Catheter Ablation in Patients with Atrial Fibrillation: A Validation Study with Electroanatomical Mapping

Abstract: This study suggested that the EMT-ε could be a useful echocardiographic marker of LA electromechanical abnormalities in patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Modern echocardiographic techniques, such as myocardial deformation indices such as Doppler-derived regional atrial strain, have also been successfully used to quantify atrial function. [ 42 43 ] Speckle tracking echocardiography (STE) is an advanced imaging technique enabling the assessment of impairment of LA reservoir function,[ 44 ] potentially caused by reduced atrial compliance due to atrial fibrosis.…”
Section: N Oninvasive I Maging ...mentioning
confidence: 99%
“…Modern echocardiographic techniques, such as myocardial deformation indices such as Doppler-derived regional atrial strain, have also been successfully used to quantify atrial function. [ 42 43 ] Speckle tracking echocardiography (STE) is an advanced imaging technique enabling the assessment of impairment of LA reservoir function,[ 44 ] potentially caused by reduced atrial compliance due to atrial fibrosis.…”
Section: N Oninvasive I Maging ...mentioning
confidence: 99%
“…4 Robust and feasible method in diagnosis of LA fibrosis is a challenge in clinical practice. 7 Speckle tracking echocardiography (STE) 5 The extent of LA fibrosis may be also assessed using an electroanatomical mapping (EAM); however, this requires invasive electrophysiological study.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the studies correlating electrophysiological and biochemical surrogate of fibrosis and echocardiographic parameters of LA, only a few data are available from invasive EAM of LA. 7 Speckle tracking echocardiography (STE)…”
mentioning
confidence: 99%
“…Thus, the probability of recurrence of AF was reduced. It has also been reported that the recurrence of AF was significantly lower in patients with shorter P-εCT than those patients with persistently longer P-εCT for 6 months (31). This also indicates that TACT could play a guiding role in the recurrence of AF after the surgery.…”
Section: Effects Of the Surgery On La Functionmentioning
confidence: 80%